Effect of silicon on morphological, physiological and biochemical characteristics in salinity tolerance in indica rice - D, Roshini; J, Anbumalarmathi (ORYZA-An International Journal of Rice, 2023)
Silicon application can increase plant tolerance to abiotic stress and enhance productivity. Seeds of two Rice varieties (ADT53: salinity susceptible and Co 53: salinity tolerance) were exposed to different concentrations of NaCl (25, 50, 75 and 100 mM), Silicon (Sodium metasilicate; 1, 1.5 and 2 mM) and a combination of both NaCl and Silicon to investigate the effect of silicon on seed germination, morphological, physiological and biochemical characteristics under salinity stress imposed for 15 days and also subjected to fresh water alone (control). Application of silicon enhances the germination rate of ADT 53 and Co 53 (90%) in 50mM NaCl + 2mM Si. Maximum shoot length was observed in ADT 53 (6.54 cm) and Co 53 (10 cm) in 25 mM NaCl + 2mM Si. Maximum root length was observed in ADT 53 (12.9 cm) and Co 53 (10 cm) in 50mM NaCl + 1mM Si. ADT 53 (33.3%) showed the highest percentage of chlorophyll-a in 25 mM NaCl + 1 mM Si and Co 53 (30%) in 75mM NaCl + 2 mM Si 100 mM NaCl + 2 mM Si. The highest percentage of Chlorophyll b was observed in ADT 53 (104%) in 25 mM NaCl + 2mM Si and Co 53 (95%) in 100 mM NaCl + 2 mM Si. Total chlorophyll content was maximum in ADT 53 (133%) in 25mM NaCl + 2mM Si and Co 53 (130%) in 75 mM NaCl + 2mM Si. Maximum carotenoid was observed in ADT 53 (240%) in 100 mM NaCl + 1.5 mM Si and Co 53 (273%)in 25 mM NaCl + 2 mM Si. Chlorophyll stability index was increased in ADT 53 (185.7%) in 100 mM NaCl + 2 mM Si and Co 53 (205.38%) in100 mM NaCl + 1.5 mM Si. Proline content was decreased in ADT 53(13%) in 25 mM NaCl + 1.5 mM Si and Co 53 (11%) in 100 mM NaCl + 1.5mM Si. MDA was found low in ADT 53 (11%) in 100 mM NaCl + 1.5 mM Si for and Co 53 (14%) in 50 mM NaCl + 2 mM Si. CAT activity was found low in ADT 53 (14%) in 25mM NaCl + 1.5 mM Si and Co 53 (16%) in 25 mM NaCl + 2 mM Si , 100 mM NaCl + 1.5mM Si. ADT 53 showed the on-par performance with salinity tolerant variety Co 53.